The sum of three numbers is 6, the sum of their squares is 8, and the sum of their cubes is 5. What is the sum of their fourth powers?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
As always you spot a pattern that i couldn't even think about. Your solutions are always really creative and they helped me to proper flex my pattern recognition muscle. Keep up the good work sir!
I spent a decent amount of hours trying to fully understand and internalize your solution. I'm still struggling to find out how you managed to come up with the last identity (a^4 + b^4 +c^4 = (a + b + c)([...]). Could someone shed some light on this?
Log in to reply
Refer to Newton's sums or Newton's identities .
Let the 3 numbers be a , b , c .
By using Newton's Sums we can find a polynomial P ( x having a , b , c as its zeroes.
P ( x ) = x 3 − 6 x 2 + 1 4 x − 3 4 1
By using Newton's Sum we'll get a 4 + b 4 + c 4 = 0 .
Problem Loading...
Note Loading...
Set Loading...
Let the three numbers be a , b and c . Using Newton's sums or Newton's identities , we have:
a + b + c a 2 + b 2 + c 2 6 2 − 2 ( a b + b c + c a ) ⇒ a b + b c + c a a 3 + b 3 + c 3 6 ( 8 − 1 4 ) + 3 a b c ⇒ a b c a 4 + b 4 + c 4 = 6 = ( a + b + c ) 2 − 2 ( a b + b c + c a ) = 8 = 2 3 6 − 8 = 1 4 = ( a + b + c ) ( a 2 + b 2 + c 2 − a b − b c − c a ) + 3 a b c = 5 = 3 3 6 + 5 = 3 4 1 = ( a + b + c ) ( a 3 + b 3 + c 3 − ( a b + b c + c a ) ( a 2 + b 2 + c 2 ) + a b c ( a + b + c ) = 6 ( 5 ) − 1 4 ( 8 ) + 3 4 1 ( 6 ) = 0